PENGARUH PELAYANAN, FLEKSIBILITAS PEMBAYARAN DAN PERSYARATAN PINJAMAN KREDIT TERHADAP MINAT MENGGUNAKAN LEASING FIF CABANG KETAHUN - Jeni Setiawati; Melvi Yansi; Eko Wediyanto (JURNAL MANAJEMEN MODAL INSANI DAN BISNIS (JMMIB), 2026)
This research is entitled The Influence of Service, Payment Flexibility and Credit Loan Requirements on Interest in Using Leasing Fif Branch Ketahun. The research population is all customers who take out FIF Branch Leasing credit loans, and is determined as a sample of 120 people. The data collection technique uses questionnaires and data analysis using SEM. The results of this study prove that the service has a positive and significant effect on the interest in using FIF leasing. The results of the analysis show that the services provided by the leasing party FIF Ketahun Branch make a real contribution to increasing the interest of oil palm farmers. Payment flexibility has the strongest positive and significant effect on interest in using FIF leasing. Loan terms have a positive and significant effect on interest in using FIF leasing. Service, payment flexibility, and loan terms simultaneously affect interest in using FIF leasing. Simultaneously, the three independent variables were able to explain 61.5% of the variation in customer interest in Ketahun's District (R-Square 0.615). This confirms that the combination of excellent service, adaptive payment system, and simple requirements procedures is a very effective and powerful strategy in encouraging oil palm smallholders' interest in using FIF Ketahun's Branch leasing services. Keywords: Service, payment flexibility, loan terms and interest in reuse